2021
DOI: 10.1038/s41598-021-84545-7
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative molecular detection of larval Atlantic herring (Clupea harengus) in stomach contents of Atlantic mackerel (Scomber scombrus) marks regions of predation pressure

Abstract: Mortality rates in the early life-history stages of fishes are generally high yet identifying the causes remain unclear. Faltering recruitment rates of Atlantic herring (Clupea harengus) in the Norwegian Sea indicate a need to identify which mortality factors influence larval herring survival. Previous research suggests that increased predation pressure by Atlantic mackerel (Scomber scombrus) may contribute to the disconnect between spawning stock biomass and recruitment. To quantify the contribution of predat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 54 publications
0
14
0
Order By: Relevance
“…This CIA projected the pelagic complex to respond favourably to warming (Figure 5b), with strengthened northward feeding migration of adult mackerel (Nøttestad et al., 2016) (Appendix S1, Stock Narratives). However, this increased prey field may intensify mackerel predation on Norwegian spring‐spawning herring larvae reducing subsequent recruitment success (Allan et al., 2021).…”
Section: Resultsmentioning
confidence: 99%
“…This CIA projected the pelagic complex to respond favourably to warming (Figure 5b), with strengthened northward feeding migration of adult mackerel (Nøttestad et al., 2016) (Appendix S1, Stock Narratives). However, this increased prey field may intensify mackerel predation on Norwegian spring‐spawning herring larvae reducing subsequent recruitment success (Allan et al., 2021).…”
Section: Resultsmentioning
confidence: 99%
“…Bottomup factors, such as changes in temperature and shifts in the abundance and type of prey, have been proposed as potential drivers of recruitment variability in these populations (Cardinale et al 2009). Other studies have suggested that cannibalism and predation from other forage fishes (e.g., Atlantic mackerel, Scomber scombrus) can have a large impact on larval survival (Allan et al 2021), but the ultimate consequences for recruitment and the relative contribution of each process is still largely unknown (Corten 2013;Skaret et al 2015;Garcia et al 2020). In general, it is now clear that the set of recruitment drivers is highly context-dependent, varying in time and space within and among populations (e.g., Zimmermann et al 2019).…”
Section: Introductionmentioning
confidence: 99%
“…The NSS herring population and its environment have undergone drastic changes over the course of the 80 years study period, including the onset of industrial fishing, a population collapse in the late 1960's followed by a full recovery in 1990's, a warming trend over the past decades, and the habitat expansion of the Northeast Atlantic mackerel as a potential competitor and predator of herring eggs and larvae (Skaret et al 2015, Bachiller et al 2016, Allan et al 2021. Considering that growth is the product of an organisms entire life history and the environment it is experiencing (Enberg et al 2012), it is likely that NSS herring has adapted to the changes it has experienced over time.…”
Section: Discussionmentioning
confidence: 99%